Microbiological Safety and Health Properties of Marketed Fermented Root Vegetables - Eliza Knez; Rafał Hałasa; Katarzyna Turecka; Justyna Ośko; Kornelia Kadac-Czapska; Krzysztof Waleron; Małgorzata Grembecka (Applied Sciences)
The study aimed to evaluate the antioxidant potential and microbial composition of edible fermented vegetable roots available on the Polish market, including celeriac, carrot, beetroot, radish, and white radish. The microbiological determinations were conducted according to European Standards. The total phenol content (TPC) was measured by the Folin–Ciocalteu (FC) method, while the total antioxidant capacity (TAC) was analyzed by CUPRAC and DPPH assays. The mean recovery for FC, CUPRAC, and DPPH was in the range of 104–105%, 97–102%, and 96–108%, while the precision amounted to 2.3, 2.75, and 5.99, respectively. The average antioxidant potential among all fermented roots decreased in the following order: beetroot > celeriac > radish > carrot > white radish. In the case of microbiological analyses, no bacteria were found in pasteurized products. However, among unpasteurized vegetables, 7 out of 11 products met the FAO/WHO criteria for probiotic foods, as they contained a sufficient number of lactic acid bacteria and lacked Escherichia coli. None of the tested products were contaminated with Bacillus cereus, Salmonella spp., Enterococcus spp., or spore-forming anaerobic bacteria. Moreover, chemometric techniques such as the Kruskal–Wallis test and cluster analysis were used to differentiate samples in view of their antioxidant potential. These analyses demonstrated the similarity of vegetable samples from the Apiaceae and Brassicaceae families while highlighting differences in antioxidant potential compared to samples from the Amaranthaceae family.